2022
DOI: 10.1111/jen.13087
|View full text |Cite
|
Sign up to set email alerts
|

Differential resistance across paternal genotypes of honey bee brood to the pathogenic bacteriumMelissococcus plutonius

Abstract: The bacterium Melissococcus plutonius is the causative agent of European foulbrood (EFB), a disease affecting immature stages (i.e., brood) of honey bees (Forsgren, 2010). This gram-positive bacterium is transmitted by symptomless adult honey bees to young larvae, which become infected after ingesting the pathogen through contaminated food. The bacterium then multiplies in the larvae's gut, which can lead to their death. As a result, within-colony population dynamics are disturbed, to the point that colonies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…M. plutonius is often described as an opportunistic pathogen that is triggered to cause EFB disease based on a combination of nutritional deficiencies, 16,24,60 pathogen genotype, 61,62 and host genotype, 63 among other factors. Given the possible connection with nutrition, it is conceivable that inopportune foraging conditions could promote disease and increase M. plutonius occurrence, but it has been suggested that strong nectar flows might actually also promote M. plutonius proliferation due to diversion of nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…M. plutonius is often described as an opportunistic pathogen that is triggered to cause EFB disease based on a combination of nutritional deficiencies, 16,24,60 pathogen genotype, 61,62 and host genotype, 63 among other factors. Given the possible connection with nutrition, it is conceivable that inopportune foraging conditions could promote disease and increase M. plutonius occurrence, but it has been suggested that strong nectar flows might actually also promote M. plutonius proliferation due to diversion of nursing care.…”
Section: Discussionmentioning
confidence: 99%